2012
DOI: 10.7314/apjcp.2012.13.4.1217
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Oral Cancer Awareness and Early Detection using a Mass Media Approach

Abstract: Background and Aim: Less than 50% of oral cancer cases are diagnosed at early stages of the disease and this is in part due to poor awareness and lack of knowledge on the signs and symptoms of oral cancer. This study sought to measure the baseline awareness of oral cancer in Malaysia and aimed to increase public awareness and knowledge of oral cancer using a mass media campaign. Methods: Baseline awareness and impact of the campaign was measured using self-administered questionnaires sent via email to individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 23 publications
(17 reference statements)
8
45
1
2
Order By: Relevance
“…These results support previous findings, which report that mass media is a common source of information regarding oral cancer (Peker and Al-Kurt 2010;Park et al, 2011;Ghani et al, 2013;Tadbir et al, 2013). A recent Malaysian study has assessed the impact of promoting oral cancer awareness of the public using a mass media campaign; the results showed a significant increase in the public awareness regarding general knowledge and etiology factors of the disease (Saleh et al, 2012). Furthermore, another study has reported that television advertising offered the largest coverage in an oral cancer awareness campaign in comparison to other (Eadie et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results support previous findings, which report that mass media is a common source of information regarding oral cancer (Peker and Al-Kurt 2010;Park et al, 2011;Ghani et al, 2013;Tadbir et al, 2013). A recent Malaysian study has assessed the impact of promoting oral cancer awareness of the public using a mass media campaign; the results showed a significant increase in the public awareness regarding general knowledge and etiology factors of the disease (Saleh et al, 2012). Furthermore, another study has reported that television advertising offered the largest coverage in an oral cancer awareness campaign in comparison to other (Eadie et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Only less than quarter of the participants knew that presence of red and or white patches was early signs of oral cancer. These findings are consistent with most of the published studies that reported lack of public knowledge regarding early signs of oral cancer (Tomar et al, 2005;Devadiga and Prasad 2010;Pakfetrat et al, 2010;Park et al, 2011;Agrawal et al, 2012;Saleh et al, 2012;Tadbir et al, 2013;Quadri et al, 2014). Such findings indicate that there is not enough attempt on giving information about first signs of oral cancer, and that is why most of people have not enough information about that (Tadbir et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Under certain circumstances, the media can contribute to amplifying the community agenda for social changes (Demers and Viswanath, 1999;Nessa et al, 2013;Saleh et al, 2012). Organized efforts for the promotion of public health, such as population-based health communication campaigns, often use the mass media as a powerful tool (Beaudoin et al, 2006).…”
Section: Media Advocacymentioning
confidence: 99%
“…The validated questionnaires were distributed to 988 practising dentists in Malaysia who attended two major dental conferences organised by the Malaysian Dental Association (MDA) held in Kuala Lumpur and in Kota Kinabalu, Sabah, Malaysia. The sample size for this study was calculated using a single proportion formula, based on the proportion of awareness among adults in Malaysia of 80% (Saleh et al, 2012) at the precision of 5% giving a total of 245 subjects. Pearson's chi-square and KruskalWallis tests were conducted to evaluate the association between dentists' background [gender, year and country/ region of graduation, participation in continuous medical education (CME)] and their knowledge and practice of early detection and prevention of oral cancer (knowledge on early signs and symptom, knowledge on risk factors, conducting opportunistic screenings and providing risk habits cessation).…”
Section: Methodsmentioning
confidence: 99%